Ketohexokinase inhibition improves NASH by reducing fructose-induced steatosis and fibrogenesis - Shepherd, Emma L.; Saborano, Raquel; Northall, Ellie; Matsuda, Kae; Ogino, Hitomi; Yashiro, Hiroaki; Pickens, Jason; Feaver, Ryan E.; Cole, Banumathi K.; Hoang, Stephen A.; Lawson, Mark J.; Olson, Matthew; et al. (JHEP reports, 2021)
Increasing evidence highlights dietary fructose as a major driver of non-alcoholic fatty liver disease (NAFLD) pathogenesis, the majority of which is cleared on first pass through the hepatic circulation by enzymatic phosphorylation to fructose-1-phosphate via the ketohexokinase (KHK) enzyme. Without a current approved therapy, disease management emphasises lifestyle interventions, but few patients adhere to such strategies. New targeted therapies are urgently required. We have used a unique combination of human liver specimens, a murine dietary model of NAFLD and human multicellular co-culture systems to understand the hepatocellular consequences of fructose administration. We have also performed a detailed nuclear magnetic resonance-based metabolic tracing of the fate of isotopically labelled fructose upon administration to the human liver. Expression of KHK isoforms is found in multiple human hepatic cell types, although hepatocyte expression predominates. KHK knockout mice show a reduction in serum transaminase, reduced steatosis and altered fibrogenic response on an Amylin diet. Human co-cultures exposed to fructose exhibit steatosis and activation of lipogenic and fibrogenic gene expression, which were reduced by pharmacological inhibition of KHK activity. Analysis of human livers exposed to 13C-labelled fructose confirmed that steatosis, and associated effects, resulted from the accumulation of lipogenic precursors (such as glycerol) and enhanced glycolytic activity. All of these were dose-dependently reduced by administration of a KHK inhibitor. We have provided preclinical evidence using human livers to support the use of KHK inhibition to improve steatosis, fibrosis, and inflammation in the context of NAFLD. We have used a mouse model, human cells, and liver tissue to test how exposure to fructose can cause the liver to store excess fat and become damaged and scarred. We have then inhibited a key enzyme within the liver that is responsible for fructose metabolism. Our findings show that inhibition of fructose metabolism reduces liver injury and fibrosis in mouse and human livers and thus this may represent a potential route for treating patients with fatty liver disease in the future. [Display omitted] •Mice deficient in ketohexokinase (KHK) show reduced features of NASH on a high-fat/high-fructose diet.•KHK inhibition reduces lipogenic gene expression in the presence of high fructose/glucose.•Activated myofibroblasts show reduced expression of fibrogenic genes when treated with KHK inhibitor.•KHK inhibitor reduced hepatic accumulation of lipogenic fructose derivatives and glycolysis in human liver.